Factors influencing behaviour to participate in Islamic microfinance - Maulana, Hartomi; Abdul Razak, Dzuljastri; Adeyemi, Adewale Abideen (Emerald Group Publishing Ltd., 2018)
Purpose – The purpose of this paper is to empirically examine the factors that affect Muslim customers’ participation in using Baitul Maal wat Tamwil (BMT). The decomposed theory of planned behaviour (DTPB) was used as the research framework. Design/methodology/approach – The paper uses primary data collected by self-administered questionnaires involving a sample of 405 respondents from selected BMTs in five different regencies in East Java. Structural equation modelling was used in the analysis. Findings – This study revealed that among the three main beliefs, only perceived behavioural control towards BMT was found to have positive and significant impact on clients’ participation towards BMT. With regards to antecedents’ influence on their main beliefs, only perceived compatibility, perceived complexity and uncertainty and facilitating condition were not significant. Research limitations/implications – As the data collected are existing clients of BMT, behavioural intention is excluded from the study, and as a result, the study may lack comprehensive results. Therefore, future study will be very useful if it includes behavioural intention as the variables. Practical implications – The finding of the present study could help BMT to better manage by focussing on relative advantage and behavioural control to build client relationships. Originality/value – The paper may be first study to apply DTPB to client behaviours in the area of Islamic microfinance in Indonesia.